An Organizational Model for Excellence in Healthcare Delivery: Evidence From Winners of the Baldrige Quality Award. Issue 5 (September 2017) - Griffith, John R.
Abstract : EXECUTIVE SUMMARY: Winners of the Baldrige National Quality Award in healthcare have documented top quartile clinical outcomes and patient satisfaction across a variety of American communities and a full spectrum of care. Their results also show high levels of satisfaction among physicians, nurses, and other workers, as well as effective financial performance. The managerial methods they use—collectively, the Baldrige model—are consistent with organizational theory literature and are found across all winners. The winners have sustained excellence after winning and expanded it by acquisition of other healthcare organizations. The model differs substantially from traditional management approaches in healthcare delivery. It is a comprehensive program that emphasizes a shared focus on excellence, systematically responsive management, evidence-based medicine, multidimensional measures and negotiated goals, improvement of work processes, thorough training, and extensive rewards. The model could be expanded on a much larger scale. Doing so successfully would substantially improve the quality and cost of healthcare, as well as the satisfaction and commitment of care providers and other staff. The opportunity deserves further study and trial by large healthcare delivery systems, insurers, and consulting companies.